A recombinant antigen-based enzyme-linked immunosorbent assay (ELISA) for lungworm detection in seals. Issue 1 (December 2015) - Ulrich, Sophia; Lehnert, Kristina; Siebert, Ursula; Strube, Christina
Abstract Background Pinnipeds are frequently infected by the lungwormsOtostrongylus circumlitus andParafilaroides gymnurus (Metastrongyloidea). Infections are frequently associated with secondary bacterial bronchopneumonia and are often lethal. To date, a reliable lungworm diagnosis in individual seals is only possible during necropsy as examination of faeces collected from resting places does not allow assignment to individuals. Therefore, a diagnostic tool for lungworm detection in living seals is desirable for monitoring health of seals in the wild and in captivity. Previously, an ELISA based on recombinant bovine lungworm major sperm protein (MSP) as diagnostic antigen was developed for lungworm diagnosis in cattle. In the present study, this test was adapted for detection of antibodies against lungworms in harbour (Phoca vitulina ) and grey seals (Halichoerus grypus ). Furthermore, sera of northern elephant seals (Mirounga angustirostris ) were tested to evaluate whether the harbour/grey seal ELISA is suitable for this seal species as well. Methods For ELISA evaluation, lungworm-positive and -negative sera of harbour and grey seals were analysed using horseradish peroxidase (HRP)-conjugated Protein A as secondary antibody. Optical density was measured and a receiver operating characteristic (ROC) analysis was performed to determine a cut-off value. Potential cross-reactions were examined by testing serum of seals positive for gastrointestinal and heart nematodes, but negative for lungworm infections. In addition, sera of northern elephant seals were analysed. Results Harbour and grey seal serum samples showed significant differences in optical density (OD) between serum of infected and uninfected animals resulting in a cut-off value of 0.422 OD with a specificity of 100 % (95 % CI: 87.23-100 %) and a sensitivity of 97.83 % (95 % CI: 88.47-99.94 %). Cross-reactions with heart or gastrointestinal nematodes were not observed. Analysis of northern elephant seal samples resulted in detection of antibodies in animals positive for lungworm larvae at faecal examination. Conclusions The ELISA presented is a valuable method for detection of lungworm infections in live harbour and grey seals, providing a monitoring tool to reveal epidemiological dynamics of lungworm infections during health surveillance in free-ranging seals. Furthermore, ELISA results may aid institutions with harbour and grey seals under human care on decisions regarding anthelminthic treatment of individual animals.